The tectonic development of the Namaqua mobile belt and its foreland in parts of the Northern Cape - Vajner, Václav (Department of Geological Sciences, 2016)
The Namaqua Mobile Belt extends from the south-western coast of Southern Africa through northern Namaqualand and adjacent parts of South West Africa to the south-western margin of the Kaapvaal Craton near Prieska. Its Precambrian tectonic development is characterised by several successive periods of deformation and metamorphism, the last of which - the Namaqua tectogenesis - occurred between c. 0,9 and 1,25 Ga B.P. The northern boundary of the mobile belt is the Namaqua front which, at different places along its length, appears as a metamorphic transition, as an oblique-slip fault, and as an interface between areas yielding radiometric ages of 2,5 - 2,9 Ga and 0,9- 1,25 Ga respectively. The foreland of the belt in the area under consideration is formed by the south-western marginal part of the Kaapvaal Craton and by the Kheis tectonic domain; the former comprises granitoids and metamorphites generally older than c.2,5 Ga (the Skalkseput Granite, the Draghoender Granite and the Swartkop sequence), as well as supracrustal cover-rocks ranging in age between c. 2,5 and 1,8 Ga (the Seekoebaard Formation, the Transvaal Supergroup and the Matsap Formation). The area of the latter is underlain by a sequence of metasediments and metavolcanics (the Kheis Group), which has been deformed and metamorphosed prior to the deposition of the Seekoebaard Formation (probably prior to the intrusion of the Draghoender Granite c. 2,9 Ga B.P.).